Substâncias húmicas de turfa: estudo dos parâmetros que influenciam no processo de extração alcalina - Rosa, André Henrique [UNESP]; Rocha, Julio Cesar [UNESP]; Furlan, Maysa [UNESP] (Sociedade Brasileira de Química, 2000)
This study reports the parameters which influence on extraction of humic substances (HS) from peat. The yield, organic and inorganic contend, E4/E6 ratio and elemental composition (C,H,N) of the extracted HS have been determined. The functional groups were identified by Fourier-transform infrared espectroscopy. The results showed influence of the extractor type, concentration, time, temperature and granular texture of the sample in the extraction. This work contributes to better understanding of the extraction process showing the necessity of the standard method to extract humic substances from soil
Humic substances of peat: study of the parameters that influence on the process of alkaline e extraction
Keywords: humic substances; humic acid; fulvic acid; peat; extraction